Peningkatan pemahaman konsep matematika padaMateri relasi dan fungsi melalui pendekatan Realistic Mathematics Education (RME) - Daaliuwa, Ica Pratika; Ismail, Sumarno; Takaendengan, Bertu Rianto (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to improve the understanding of mathematical concepts in relation and function material the Realistic Mathematics Education (RME) approach. This Classroom Action Research was conducted at one of the junior high schools in Suwawa for the 2023/2024 academic year within two cycles. The subjects were 24 students in grade VIII 3 and a mathematics teacher. Data collection in this study was carried out through observation and tests. Consisting of observation sheets of teacher activities, students, and essay. From the observations, teacher activity increased by 12% from cycle 1(77% with the “good” category) to cycle II (89% with the “very good”category) and student activities increased by 27% from cycle 1 (60% with the “good” category) to cycle II (87% with “the very good” category). Likewise, students’ abilities to understand mathematical concept increased by 12% from 74% in cycle I to 86% in cycle II. Thus, there is a significant increasein the understanding of mathematical concept through the Realistic Mathematics Education (RME) approach.